Adaptabilities of different harvesters to peanut plants after cutting stalks - Chen, Youqing; Wang, Gongpu; Wang, Jiangtao; Zhang, Peng; Wang, Bing; Hu, Zhichao (International Journal of Agricultural and Biological Engineering, 2022)
At present, there are no harvesters specifically adapted to process peanuts after cutting stalks. In particular, methods for harvesting peanuts after cutting stalks have not been reported thus far. Therefore, to utilize peanut stalks as feed when harvesting plastic-film-grown peanuts, and to improve industry benefits, a three-stage harvesting method is proposed herein. In view of the three-stage harvesting method, the peanut stalks are cut before digging, with the remaining peanut plants being shorter, thereby increasing the peanut pod-stalk ratio. To investigate the adaptabilities of existing harvesters in harvesting peanuts after cutting stalks, three types of peanut harvesters—the self-propelled pick-up combine harvester, trailed pick-up combine harvester, and peanut picker were used to conduct a comparative test on harvesting intact peanut plants and plants after cutting stalks. The loss, breakage and impurity rates were used as evaluation indicators. The loss rates of these three harvesters were 14.64%, 16.44% and 1.33%; the breakage rates were 21.28%, 21.92% and 20.00%, and impurity rates were 4.60%, 8.76% and 9.06%. Analysis of variance showed that cutting stalks had a significant impact on the work qualities of the three harvesters (p < 0.05). With regard to the loss rate, results revealed that: the two peanut combine harvesters could not be adapted to harvest peanut plants after cutting stalks. The three harvesters had good adaptability to harvest peanut plants after cutting stalks, considering the breakage rate; however, based on the impurity rate, the three harvesters could not be adapted to harvest peanut plants after cutting stalks. The losses of the two combine harvesters consisted mainly of dropped and missed picking, with the sum of the losses accounting for 99.87% and 97.99% of the total losses of the two harvesters, respectively; this suggests that the drum pickup of the combine harvesters could not adapt to harvesting the peanut after cutting stalks. The breakage rates of the three harvesters were considerably reduced, suggesting that the pod picking devices of the three harvesters were suitable for harvesting the peanut after cutting stalks; the impurity rates of the three harvesters were considerably increased, indicating that the pod picking and cleaning devices of the three harvesters were not suitable for harvesting peanut after cutting stalks. To improve the adaptabilities of the harvesters, it is suggested that the speed of pickup elastic tooth, lateral spacing between adjacent elastic teeth, concave screen hole size of pod picking device, the structure and motion parameters of cleaning device should be optimized. The results of this study provide a reference for the development and improvement of peanut harvesters suitable for harvesting peanuts after the cutting of stalks.Keywords: agricultural machinery, peanut, peanut harvesting after cutting stalks, peanut combine harvester, peanut picker, adaptability researchDOI: 10.25165/j.ijabe.20221502.6515Citation: Chen Y Q, Wang G P, Wang J T, Zhang P, Wang B, Hu Z C. Adaptabilities of different harvesters to peanut plants after cutting stalks. Int J Agric & Biol Eng, 2022; 15(2): 93–101.